Reformation und Säkularisierung Zur Kontroverse um die Genese der Moderne aus dem Geist der Reformation - Dalferth, Ingolf U. (Mohr Siebeck, 2017)
The Reformation was essentially a religious renewal of Christianity in Europe. As such, it has contributed decisively, along with the Renaissance and humanism, to the formation of a secular modernity. What exactly was this contribution and how is it to be assessed? Have Reformation movements destroyed the traditional unity of the church and the state, of society and culture, and in so doing instigated the marginalisation of Christianity in Europe? Or have they brought central impulses of Christianity to the fore, without which Western modernity could not developed, and which also characterise a society that understands itself as secular in a plural late modern era? The present volume attempts to shed light on these controversial questions. Criticisms levelled at reformed traditions by the secular modernism standpoint as well as those aimed at European modernity and late-modernity from the camp of reformed thinking are also given a voice.